Rational design of multifunctional Fe@γ-Fe2O3@H-TiO2 nanocomposites with enhanced magnetic and photoconversion effects for wide applications : from photocatalysis to imaging-guided photothermal cancer therapy - Wang, Meifang (2020)
Titanium dioxide (TiO2 ) has been widely investigated and used in many areas due to its high refractive index and ultraviolet light absorption, but the lack of absorption in the visible-near infrared (Vis-NIR) region limits its application. Herein, multifunctional Fe@γ-Fe2 O3 @H-TiO2 nanocomposites (NCs) with multilayer-structure are synthesized by one-step hydrogen reduction, which show remarkably improved magnetic and photoconversion effects as a promising generalists for photocatalysis, bioimaging, and photothermal therapy (PTT). Hydrogenation is used to turn white TiO2 in to hydrogenated TiO2 (H-TiO2 ), thus improving the absorption in the Vis-NIR region. Based on the excellent solar-driven photocatalytic activities of the H-TiO2 shell, the Fe@γ-Fe2 O3 magnetic core is introduced to make it convenient for separating and recovering the catalytic agents. More importantly, Fe@γ-Fe2 O3 @H-TiO2 NCs show enhanced photothermal conversion efficiency due to more circuit loops for electron transitions between H-TiO2 and γ-Fe2 O3 , and the electronic structures of Fe@γ-Fe2 O3 @H-TiO2 NCs are calculated using the Vienna ab initio simulation package based on the density functional theory to account for the results. The reported core-shell NCs can serve as an NIR-responsive photothermal agent for magnetic-targeted photothermal therapy and as a multimodal imaging probe for cancer including infrared photothermal imaging, magnetic resonance imaging, and photoacoustic imaging.